Formation of leadership among curators of sports groups - Klimenko O.E.; Fomenko E.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the characteristics that contribute to the development of leadership abilities in the leader of a student group in the sports department. Methods and structure of the study. The research project involved students from various years and academic disciplines. Sociometric techniques were employed to assess the values and position of a leader within a group. To identify the characteristics of leadership, criteria for its development were established, with specific indicators of readiness for leadership. Results and conclusions. It is clear that in order to become a leader, the mentor of the sports department’s student group must cultivate certain traits, such as a strong motivational framework that includes goal-setting, a set of values, and the distinctiveness of our work. In the hierarchy of leadership attributes, the primary factor is the ambition to excel in academic and professional pursuits.